Genially for English teaching and learning - Guillen Pisco, María Elena; Cerón Pazmiño , Ana María (SATHIRI, 2025)
Traditional English teaching methods present limitations that are aggravated by the lack of digital skills in both teachers and students. In Ecuador, this situation contributes to the low performance in this matter at the national level. Therefore, the objective of this study was to implement Genially in the teaching-learning process of English of students from an educational unit in Tulcán, in order to improve their linguistic skills. A mixed and causal approach was used, combining field and documentary methods, with a pre-experimental quasi-experimental design. Pre-Test and Post-Test were administered to 80 students. The methodology included interviews with teachers and surveys with students to evaluate their English skills. Statistical tests such as Shapiro-Wilk, Student’s t for paired samples, correlation analysis and the N-Gain formula were carried out. The results revealed low digital skills in both students and teachers, as well as a general lack of knowledge of digital tools such as Genially, which resulted in no use of them in classes. In conclusion, the skills evaluated showed a significant improvement aft’r the intervention with Genially, with an increase of 0.50 points. However, it also highlights the urgent need to train teachers to optimize its use and effectiveness in the classroom.